Integrating postural and vestibular dimensions to depict impairment in moderate‐to‐severe obstructive sleep apnea syndrome patients. (20th March 2017) - Micarelli, Alessandro; Liguori, Claudio; Viziano, Andrea; Izzi, Francesca; Placidi, Fabio; Alessandrini, Marco
Summary: Vestibular dysfunction was linked to moderate‐to‐severe obstructive sleep apnea syndrome (OSAS) patients in literature. However, due to a lack of knowledge among valid and recent implementations conceived to study postural control on static posturography (SP) and vestibulo‐ocular reflex (VOR) gain under physiological conditions (video Head Impulse Test; vHIT), the aim of this work was to integrate (i) VOR changes via vHIT implementation, (ii) postural arrangement by studying both classical parameters and frequency spectra (PS) and (iii) correlation between these findings, polygraphic (PG) and subjective scores along Dizziness Handicap Inventory (DHI) and Epworth Sleepiness Scale (ESS). Thus, 32 moderate‐to‐severe OSAS patients and 32 healthy subjects – studied by using PG, DHI and ESS – underwent vHIT and SP posturographic assessment. Analysis of variance was performed to disclose between‐group effects and correlation analysis was implemented between otoneurological, PG, DHI and ESS values. OSAS group demonstrated a significant decay of VOR gain and an increase in both frequency spectra PS values, especially within the low‐frequency interval, and in classical posturographic SP parameters. Further, positive and negative correlations between mean SaO2 and gain and low frequency interval spectra PS were found, respectively. Strengthening previous hypothesis related to brainstem chronic hypoxemia phenomena affecting vestibular network, implementation of these data could generate future attentions (i) for screening under physiological conditions postural and vestibular detriments in OSAS subjects, especially exposed at risk settings, and (ii) among PG parameters, such as mean SaO2, to propose further reliable tools in monitoring postural and vestibular decay in these patients demonstrating PG parameters detriments.